Lockdown fatigue, personal resilience and coping appraisal of faculty in a state university - Rodel Dela Cruz Afan; Jonathan Necor Tariga (Intelektual Pustaka Media Utama, 2022)
Many countries' lockdown measures have been effective in halting the spread of the coronavirus disease 2019 (COVID-19) pandemic, but there is rising worry about their negative effects on overall health and well-being, particularly among lecturer in the academe. This study aimed to assess the lockdown fatigue, personal resilience and coping appraisal involving 100 lecturers in Quirino State University-Diffun Campus. Four-likert scale questionnaires were adapted and used to gather data including the lockdown fatigue scale (LFS), brief resilience scale (BRS), and coping appraisal. Findings reveal that majority of the respondents are female, 31-40 years old, married, with an on-going Master’s Degree, with a permanent position in the university. The most prominent symptoms of fatigue, according to the respondents in this study, were worry, sadness, depression, tiredness or physical depletion, and anxiety. As to the personal resilience of lecturer, according to the findings, it is difficult for them to react quickly when anything negative occurs. As a result, efforts to reduce lockdown fatigue among lecturer must focus on developing their coping abilities, which will improve their mental and psychological well-being as well as their general health. A positive psychological intervention or program may be implemented to mitigate the negative effect brought by community lockdown.